ISLAM MASADE DI DESA LENGANENG KECAMATAN TABUKAN UTARA KABUPATEN KEPULAUAN SANGIHE - Lahindah, Patur Rahman; Kusen, Albert W. S.; Sandiah, Nasrun (HOLISTIK, Journal Of Social and Culture, 2018)
The combination Islamic beliefs and and local culture bring a distinctive image to every local religions especially in the practice of religious different in general from religion. Local community believe a function of religion or faith it is guide human life to obtain safety in the world and safety after the day of death. Claims astray and run of teachings of surely not new things in the life of the community proselyte local were not been recognized but it who is frequently in listen, but this does not cause inharmonious a relationship religious communities, like local religion who was in the area Sangihe called Islam Masade.Local religion this survives and still have a good place in the liver the Sangihe community especially the community in Lenganeng village. About the labeling a bad name to Muslims used by Islam Tua until now theological debate between Islam religions has not been discharged. Islam Masade own believe that an oral tradition or transformation followers of teaching was the doctrine left by an ancestor and verbally hereditary and must be kept. This is what make Islam Masade to be unique.The purity of the truth that applied in life of religion and participate in community events make that they exist and are still survive until now without causing conflict between groups often occurring in other regions. Until now government programs to straighten out the teachings of Islam Masade return to Islamic teachings surely did not work. Because of customary and ways of Islam Masade have viscous are both rooted in every society. Nevertheless, a relationship with Islamic mass organizations in Kecamatan Tabukan Utara established.Â Keywords: teaching, religion, disciple